A solução do sintoma ou o sintoma como solução? do sujeito em questão para a psicanálise, medicina e educação - Santos, Rosemary Jimenez Ventura dos (2013)
This work arose from the question Who is this subject that does not learn? And inspired by Lacan s researches about the logical time, it was organized and shared into three parts. The fisrt part, Instant look, deals with the questions related to learn and not learn. Beginning at the multiplicity of positions which involve this question we investigated the historical roots of the called learning problems and the contributions of the medicinal knowledge to the educational field demonstrated through diagnostics from DSM Diagnostic and Statistical Manual for mental Disorders. It was necessary to consider the education inside our present society as well as to do researches about its history in order to understand who would be these children that do not learn. This research has the purpose to study through the Psychoanalysis, its concepts and propositions, this contemporary subject whose symptom appears into this specific form: not learning. In the second part, Time to Understand, we studied the subject and their constitution to the Freud s and Lacan s Psychoanalysis, focusing in the study of the symptom too. We began at showing its origin, the place it was and is granted into the medicine and psychoanalysis and its articulations to the subject s constitution. Finally, Moment to Conclude, when we discuss the subject s specificity who does not learn through the singularity of the symptom not learning , the sense and beyond the sense, we defend the idea that the psychoanalysis brings, in critical terms, one important criticism of the diagnostic practice exercised by the medicine and psychology about the learning problems and in propositional terms, we defend the importance and the relevance of considering the subject, who does not learn, beyond the strictly observable phenomenon and beyond a reeducation therapeutics practice, enabling them a heard